Влияние содержания личинок мухи комнатной на различных субстратах на ее развитие и состояние жирового тела - Карпенко, Л.В. (Вестник зоологии, 1975)
The development and character of changes in the Musca domestica L. fatty body were studied when keeping the larvae on different substrates: beef meat (control), cotton wool cushions saturated with milk, horse manure of various freshness at temperature 28 °C. With milk diet an unusually early accumulation of fats in the larvae of age I insufficient amount and quick consumption of fat and fat-protein-glycogen reserves at the subsequent stages of ontogenesis were observed. Not fresh horse manure was defective for normal development of flies, which is confirmed by the character of changes in the larval fatty body (its size, cells' dimensions, slight accumulation and rapid consumption of reserves) and by the state of the imaginal fatty body.